The folly and the glory: America, Russia, and political warfare 1945–2020, by Tim Weiner: New York, Henry Holt and Company, 2020), 336 pp. - Bailey, Kathleen C. (Comparative Strategy, 2021)
The folly and the glory: America, Russia, and political warfare 1945-2020, by Tim Weiner: New York, Henry Holt and Company, 2020), 336 pp Why and how is Russia purposefully undermining US democracy? Weiner's final chapters outline the connections between the Trumps (both business empire and presidency) and Russia.